Thirst for reform? : private sector participation in Mexico City's water sector - Haggarty, Luke (Policy research working paper, 2001)
In the early 1990s Mexico City's Federal District (the D.F.) initiated a series of service contracts with four operators in the private sector, each to be implemented in three stages over ten years. The idea was to introduce competitive pressures and to find out if a "gradualist" aaproach would reduce social and political opposition to private sector involvement and would allow the government to address pricing problems and strengthen regulatory arrangements